Naturally Occurring Mutations in Large Surface Genes Related to Occult Infection of Hepatitis B Virus Genotype C - Kim, Hong; Lee, Seoung-Ae; Kim, Dong-Won; Lee, Sueng-Hyun; Kim, Bum-Joon (PloS one, 2013)
Molecular mechanisms related to occult hepatitis B virus (HBV) infection, particularly those based on genotype C infection, have rarely been determined thus far in the ongoing efforts to determine infection mechanisms. Therefore, we aim to elucidate the mutation patterns in the surface open reading frame (S ORF) underlying occult infections of HBV genotype C in the present study. Nested PCRs were applied to 624 HBV surface antigen (HBsAg) negative Korean subjects. Cloning and sequencing of the S ORF gene was applied to 41 occult cases and 40 control chronic carriers. Forty-one (6.6%) of the 624 Korean adults with HBsAg-negative serostatus were found to be positive for DNA according to nested PCR tests. Mutation frequencies in the three regions labeled here as preS1, preS2, and S were significantly higher in the occult subjects compared to the carriers in all cases. A total of two types of deletions, preS1 deletions in the start codon and preS2 deletions as well as nine types of point mutations were significantly implicated in the occult infection cases. Mutations within the "a" determinant region in HBsAg were found more frequently in the occult subjects than in the carriers. Mutations leading to premature termination of S ORF were found in 16 occult subjects (39.0%) but only in one subject from among the carriers (2.5%). In conclusion, our data suggest that preS deletions, the premature termination of S ORF, and "a" determinant mutations are associated with occult infections of HBV genotype C among a HBsAg-negative population. The novel mutation patterns related to occult infection introduced in the present study can help to broaden our understanding of HBV occult infections.